To solve this problem you must apply the proccedure shown below:
1. You have that [tex] f(x)=x^{3}+6x^{2}+x^{\frac{1}{2}} [/tex] and [tex] g(x)=x^{\frac{1}{2}} [/tex], therefore, you must divide must fucntion, as following:
[tex] \frac{f(x)}{g(x)}=\frac{x^{2}+6x^{2}+x^{\frac{1}{2}}}{x^{\frac{1}{2}}} [/tex]
2. You must simplify it,by factoring out [tex] x^{\frac{1}{2}} [/tex], as following:
[tex] \frac{f(x)}{g(x)}=\frac{x^{\frac{1}{2}}(
x^{\frac{5}{2}}+6x^{\frac{3}{2}}+1)}{x^{\frac{1}{2}}} [/tex]
3. Finally, you obtain that the answer is:
[tex] \frac{f(x)}{g(x)}= x^{ \frac{5}{2} } +6 x^{ \frac{3}{2} } +1[/tex]